Does diversity include me? Colorblindness and racial triangulation among Asian Americans on two college campuses. Issue 12 (25th September 2020) - Chan, Esther
ABSTRACT: Scholars have not examined to what extent racial minority students experience inclusion in diversity when they become the largest population on diverse campuses. Comparing the narratives of 26 Asian Americans on two campuses, one where they are the majority and one where they are not, reveals that numerical representation is salient for perceptions of inclusion in diversity. A focus on numerical representation supports the claim among critics that diversity is colorblind. Concurrently, Asian Americans on both campuses felt that they were not included in diversity. They explained their exclusion from diversity as the result of their cultural values and how others perceive them as the model minority. When understood alongside narratives of cultural values and the model minority myth, diversity becomes a way of signaling a racial hierarchy through a process of racial triangulation.